2021
DOI: 10.1038/s41598-021-84972-6
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic activation patterns during swallowing in older adults

Abstract: Age-related weakness due to atrophy and fatty infiltration in oropharyngeal muscles may be related to dysphagia in older adults. However, little is known about changes in the oropharyngeal muscle activation pattern in older adults. This was a prospective and experimental study. Forty healthy participants (20 older [> 60 years] and 20 young [< 60 years] adults) were enrolled. Six channel surface electrodes were placed over the bilateral suprahyoid (SH), bilateral retrohyoid (RH), thyrohyoid (TH), and ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
2
17
0
1
Order By: Relevance
“…The participants using the odor and flavor inhalation demonstrated the maximum amplitudes of muscle contractions across all testing textures of water, semi-liquid, and solid. Although evidence of this is lacking in the previous literature, similar swallowing patterns were revealed ( Ko et al, 2021 ; Molfenter et al, 2019 ). Muscular amplitudes were consistently increased in aged people while changing food/liquid viscosity or volume in swallowing.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The participants using the odor and flavor inhalation demonstrated the maximum amplitudes of muscle contractions across all testing textures of water, semi-liquid, and solid. Although evidence of this is lacking in the previous literature, similar swallowing patterns were revealed ( Ko et al, 2021 ; Molfenter et al, 2019 ). Muscular amplitudes were consistently increased in aged people while changing food/liquid viscosity or volume in swallowing.…”
Section: Discussionsupporting
confidence: 67%
“…Muscular amplitudes were consistently increased in aged people while changing food/liquid viscosity or volume in swallowing. Ko et al (2021) found that greater viscosity of bolus consistency resulted in a higher amplitude, in particular the maximum amplitude seen prior to the “main-onset” motion in a geriatric swallow. Such adaptation during the swallowing process was observable in those with presbyphagia, as well.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Koyama et al found a significantly higher prevalence of inverted muscle activation patterns in dysphagic subjects, with the activation of infrahyoid muscles preceding the suprahyoid muscles [15]. Pre-onset muscle activation is a protective mechanism to prevent neuromuscular degeneration leading to kinematic and functional loss [51] and gives rise to prolonged swallowing times, which has been widely described in dysphagic subjects [52][53][54]. In fact, the appearance of swallowing with a pre-reflex phase of muscle activation was reported as a compensatory mechanism to adjust for age-related muscle weakness [51].…”
Section: Alterations Of Muscle Interactions In Dysphagiamentioning
confidence: 99%
“…13,14 A recent study for young and older healthy populations showed that sequential contractions of the suprahyoid and infrahyoid muscles cause a circular movement of the hyoid bone during swallowing. 15,16 Hypothetically, NMES could be used not only for rehabilitation but also for the compensatory mechanism. 17,18 The compensatory mechanism of NMES means that, unlike the simultaneous stimulation of the suprahyoid and infrahyoid muscles via the conventional 2-channel NMES, the stimulation of these muscles via the sequential 4-channel NMES may lead to a better modification of the abnormal hyoid and laryngeal motion in patients with dysphagia.…”
Section: Introductionmentioning
confidence: 99%